Некоторые проблемы и перспективы биотехнологического размножения шафрана (Сrocus S.L.) - Карагезов, Т.Г.; Мамедова, М.Г.; Асадова, С.Ш.; Азизов, И.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. To develop effective approaches for biotechnological propagation of Crocus. Methods. In vitro methods for the
induction of morphogenesis and organogenesis of Crocus are used. Results. Factors influencing morphogenesis and
organogenesis of saffron (Crocus) are considered. By using a temperature qradient under in vitro conditions was obtained
de novo from 10 to 25 microcorms. Conclusions. Some issues related to biotechnology of Crocus were elucidate. The effect
of the temperature factor and selenium on the efficiency of callus formation and morphogenesis in vitro are discussed. The
methodical approaches to increase the efficiency of morphogenesis and organogenesis of Crocus in in vitro conditions were
offered.
Keywords: saffron, Crocus S.L., in vitro, morphogenesis, temperature qradient.